Integrated management of insect pests on canola and other Brassica oilseed crops - Reddy, Gadi V. P. (CABI, 2017)
This book contains 25 chapters focusing on the major insect pests of rape and other Brassica oilseed crops and the benefits of the judicious integration of various methods in the control of these damaging pests.